2017
DOI: 10.1155/2017/2370763
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polymer-Fiber Stabilization on the Unconfined Compressive Strength and Shear Strength of Sand

Abstract: The mixed soil stabilizer of polyurethane organic polymer and polypropylene fiber was used to reinforce sand. The unconfined compressive test and direct shear test were carried out to evaluate the effects of polymer-fiber reinforced sand. The different contents of polymer and fiber were selected for the tests. The test results indicated that polymer-fiber mixture can improve strongly the strength of sand. The presence of polyurethane organic polymer enhances sand structural stability and the best composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…To mitigate fracture in the treated surface due to deformation caused by human activity and traffic, we employ a "double-network" design that utilizes milli-/micro-scale polymer network to reinforce the inorganic-cemented soil network with "ductility", inspired from microfiber reinforcement of concretes, where polymer microfibers provide ductility in concrete matrix and sandy soil (Durairaj and Janaki Sundaram, 2015;Liu et al, 2017). These treatments are proven to be capable of transforming matrix bulk characteristics from brittle to malleable, which provide impact dissipation ability and prevent crack or fracture upon external strain.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate fracture in the treated surface due to deformation caused by human activity and traffic, we employ a "double-network" design that utilizes milli-/micro-scale polymer network to reinforce the inorganic-cemented soil network with "ductility", inspired from microfiber reinforcement of concretes, where polymer microfibers provide ductility in concrete matrix and sandy soil (Durairaj and Janaki Sundaram, 2015;Liu et al, 2017). These treatments are proven to be capable of transforming matrix bulk characteristics from brittle to malleable, which provide impact dissipation ability and prevent crack or fracture upon external strain.…”
Section: Introductionmentioning
confidence: 99%
“…The test results revealed that in both direct shear test and triaxial tests, the addition of fibers improved shear strength parameters and also limited the amount of post-peak reduction in shear resistance. Eldesouky et al [10], Wei Shao et al [11] and Jin Liu et al [12] studied the effects of reinforcement on strength behavior of sand. The results showed that the fiber inclusion improved the shear strength and dilation.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture of the polymer and water had the capability to enwrap the bentonite-sand particles and could result in a more compact structure. As the polymer content increased, the polymer amount mixed with water also increased and this mixture blocked the voids among the bentonite-sand particles [4]. This interlocking effect that could cause stronger bonding in the structure might be the main reason for the increase in the shear strength of the bentonite-sand mixture due to polymer addition.…”
Section: Test Results and Discussionmentioning
confidence: 98%
“…On the other hand, the increase in the cohesion due to the polymer treatment could be attributed to the stronger interaction between the polymer and the bentonite-sand particles when compared with the interaction of the bentonite-sand mixtures [17]. However, the decrease in the internal frictional angle occurred due to a possible formation of smoother surfaces of the sand particles as the polymer was added to the mixture [4].…”
Section: Test Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation